Pengembangan bahan ajar open-ended melalui polysynchronous learning berbantuan canvas - Reni Dwi Susanti; Siti Khoiruli Ummah (JINoP (Jurnal Inovasi Pembelajaran), 2021)
The current Covid-19 pandemic has severely impacted education where learning must be carried out online. Canvas is among polysynchronous e-learning platforms available. This study aims to describe the effectiveness of open-ended teaching materials through Canvas-assisted Polysynchronous Learning. This topic was chosen considering the importance teaching materials to support the implementation of Polysynchronous Learning. This study developed learning modules and power points as learning media, and Google form as evaluation media. Research and Development (R&D) approach was employed with ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. These materials were validated by material and media experts to measure their effectiveness. Results show that the teaching materials are valid and feasible. These teaching materials were implemented through a polysynchronous learning where student activities reached 89%. It is implied that these materials could enhance student learning. Students’ learning outcomes (final test) are categorized good with the average score of 80.8; the distribution of 44 points for A, 24 for B+, and 12 for B.